Comparing the generalized Kadanoff-Baym ansatz with the full Kadanoff-Baym equations for an excitonic insulator out of equilibrium - Tuovinen, Riku; Golez, Denis; Eckstein, Martin; Sentef, Michael A. (Physical Review B, 2020)
We investigate out-of-equilibrium dynamics in an excitonic insulator (EI) with a finite-momentum pairing perturbed by a laser-pulse excitation and a sudden coupling to fermionic baths. The transient dynamics of the excitonic order parameter is resolved using the full nonequilibrium Green's function approach and the generalized Kadanoff-Baym ansatz (GKBA) within the second-order Born approximation. The comparison between the two approaches after a laser-pulse excitation shows a good agreement in the weak and the intermediate photodoping regime. In contrast, the laser-pulse dynamics resolved by the GKBA does not show a complete melting of the excitonic order after a strong excitation. Instead we observe persistent oscillations of the excitonic order parameter with a predominant frequency given by the renormalized equilibrium band gap. This anomalous behavior can be overcome within the GKBA formalism by coupling to an external bath, which leads to a transition of the EI system toward the normal state. We analyze the long-time evolution of the system and distinguish decay timescales related to dephasing and thermalization.
CRIS-Team WoS Importer:2020-10-16